Low estradiol levels escalate menopausal symptoms leading to mild cognitive impairment in postmenopausal women (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Women in menopause experience dramatic alterations in gonadal hormone concentrations, including diminished estradiol levels. It has been hypothesized that these hormonal changes may be responsible for the occurrences of menopausal symptoms, such as hot flushes, sleep disruption, night sweats, and irritability, as well as mild cognitive impairment (MCI) in postmenopausal women. Therefore, this study was aimed to determine if there is any association between hormonal changes and menopausal symptoms, including MCI in postmenopausal women. METHODS A total of 245 postmenopausal women were recruited for this cross-sectional study and classified into 2 groups; MCI and non-MCI groups. Diagnosis of MCI was made using the modified Petersen criteria. Variables such as subjects’ age, duration of menopause, menopausal symptoms, anthropometric status, hormone levels, and cognitive status were assessed and statistically analyzed. RESULTS Of the 245 subjects enrolled in this study, 53.9% had MCI. Multivariate analysis found that sleep disruption and estradiol levels were independent risk factors of MCI in postmenopausal women. No significant correlation was found between menopausal symptoms and estradiol concentration. CONCLUSIONS Low estradiol levels were associated with higher risks of experiencing menopausal symptoms and MCI. Sleep disruption and estradiol levels were the most influential factors in the development of MCI in postmenopausal women.